Project Based Learning in Tourism Geography Lectures To Sharpen the Skills of 21st Century Students in the Era of the Independent Learning Curriculum - Partini, Dwi (Journal of Geography Science and Education, 2023)
Today's education is faced with the challenges of contemporary developments, currently entering an era of hyper-globalization. The government is fully aware of the future life challenges that today's young generation will face. So the government adopted a strategic policy in the world of education, namely by implementing an independent learning curriculum. Through the implementation of the independent learning curriculum, it is hoped that it can equip students with the skills needed to answer future challenges. One way to implement the independent learning curriculum is by using learning models that are relevant to the objectives of the curriculum. Project based learning is one of the learning models that is considered relevant for achieving the goals of the independent learning curriculum. Through project-based learning, can help hone the 6C skills (Character, Citizenship, Critical Thinking, Creativity, Collaboration, Communication) in this era of independent learning.